Multiple Myeloma Secondary to Systemic Lupus Erythematosus and Sjögren’s Syndrome: A Case Report - Jia WANG; Xi XIE; Fen LI; Jinwei CHEN (Archives of Rheumatology, 2014)
Patients with rheumatic diseases are at an increased risk for malignant lymphoproliferative disease, but the coexistence of rheumatic diseases and multiple myeloma is uncommon. Herein, we report a rare case of systemic lupus erythematosus and Sjögren’s syndrome, which preceded the development of multiple myeloma after three years. We also summarize the clinical features of this case and discuss the possible pathogenetic mechanisms that underlie this unusual association.